Faktor-Faktor yang Mempengaruhi Pelaporan Terintegrasi - Lawrence Chika Milenxi; Etty Murwaningsari (JPEKA: Jurnal Pendidikan Ekonomi, Manajemen dan Keuangan, 2023)
The growing needs of stakeholders make companies have to present and state financial and non-financial data comprehensively and related to conditions that occur in an integrated manner to assist stakeholders in knowing the condition of an entity properly and correctly. In Indonesia, there are still not many companies that implement integrated reporting. The purpose of this research is to collect empirical evidence about the impact of various factors on integrated reporting. These factors include green innovation, green human capital, green structural capital, green relational capital, green organizational culture as well as green supply chain management. This research consists of a quantitative descriptive aspect. The list of companies on IDX for 2020-2021 is the population in this research. The sampling technique for this research, the researcher applied purposive sampling based on the analytical method, namely multiple linear regression, classical assumption test, and multiple hypothesis testing using the Statistical Program for Social Science version 22 feature in testing the hypotheses in this research. Green innovation, green organizational culture and green supply chain management are all factors that have no impact on integrated reporting, in contrast to green human capital, green structural capital and green relational capital which have an impact on integrated reporting.